2004
DOI: 10.1002/gcc.20055
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic changes in nonmalignant breast tissue

Abstract: Cytogenetic changes are common in breast cancer and have also been described in fibroadenomas and fibrocystic disease, but not in histologically normal breast tissue. Cytogenetic analysis was performed on nonmalignant breast tissue from benign breast lumps (n = 8), reduction mammoplasties (n = 31), and grossly nontumorous tissue from cancerous breasts (n = 84), using standard techniques and G-banding. All samples were reviewed histologically. Clonal chromosomal changes were found in three of eight benign breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…It was also shown that chromosomal instability was significantly associated with presence of somatic TP53 mutations and that tumors from carriers of the Icelandic founder mutation in BRCA2, 999del5, had particularly complex chromosomal changes (Gretarsdottir et al, 1998;Eyfjord and Bodvarsdottir, 2005). We also reported an unexpectedly high proportion (15%) of cytogenetic abnormalities in histologically normal breast epithelium (Steinarsdottir et al, 2004). Prompted by these findings we have in the current study analyzed data from altogether 203 breast cancer patients with a follow-up period of 9-18 years and tested for associations between cytogenetic changes and various clinical, pathological, and genetic parameters as well as survival with the aim to shed some light on the biological and clinical significance of cytogenetic changes in nonmalignant breast tissue and breast cancer.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…It was also shown that chromosomal instability was significantly associated with presence of somatic TP53 mutations and that tumors from carriers of the Icelandic founder mutation in BRCA2, 999del5, had particularly complex chromosomal changes (Gretarsdottir et al, 1998;Eyfjord and Bodvarsdottir, 2005). We also reported an unexpectedly high proportion (15%) of cytogenetic abnormalities in histologically normal breast epithelium (Steinarsdottir et al, 2004). Prompted by these findings we have in the current study analyzed data from altogether 203 breast cancer patients with a follow-up period of 9-18 years and tested for associations between cytogenetic changes and various clinical, pathological, and genetic parameters as well as survival with the aim to shed some light on the biological and clinical significance of cytogenetic changes in nonmalignant breast tissue and breast cancer.…”
Section: Introductionsupporting
confidence: 61%
“…Culture methods were described in our previous publications (Steinarsdottir et al, 1995(Steinarsdottir et al, , 2004. Briefly, following overnight digestion in collagenase samples were cultured in Vitrogen-coated flasks (Nunc 25 cm 2 ) for 4-22 days.…”
Section: Culture Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, abnormalities have been appreciated in histologically normal breast epithelium. These abnormalities include allelic imbalance or loss of heterozygosity, [1][2][3][4][5][6][7][8] aberrant methylation of p16 INK4 9 and of RASSF1A, 10 cytogenetic changes, 11,12 telomere shortening, 13 loss of IGF2 imprinting, 14 aberrant response to estrogen, 15 loss of RARb expression, 16 aberrant phosporylation of p38, 17 upregulation of EZH2. 18 Some of these abnormalities have been detected in normal-appearing tissue adjacent to the tumor, and others have been found at a distance from it.…”
mentioning
confidence: 99%
“…The few studies comparing these groups have examined allelic imbalance, aneuploidy and methylation or expression of specific proteins, and have found abnormalities more frequently in patients with cancer than in controls. 7,8,10,12,[17][18][19] We hypothesized that by taking a comprehensive gene expression approach, we might detect consistent abnormalities in the normal-appearing epithelium of breast cancer patients, compared to controls. These abnormalities might suggest mechanisms predisposing to cancer, or activated early in carcinogenesis.…”
mentioning
confidence: 99%